Francis R. Valeo papers - Valeo, Francis R. (Francis Ralph), 1916-2006.
Correspondence, agenda, reports and other writings, subject and travel files, bibliographies, photographs, and other papers documenting Valeo's career as an East Asian specialist with the Library of Congress Legislative Reference Service, foreign affairs advisor to Senate Majority Leader Mike Mansfield, and secretary of the U.S. Senate; and Valeo's postretirement activities as a consultant in Chinese and Asian affairs. Includes material on political, economic, and military affairs in East Asia following World War II, especially in China, Japan, Korea, and the Philippines; senate files relating to Democratic party strategy, East Asian policy, the Vietnamese conflict, and the Commission on the Operation of the Senate; three senate leadership missions to China (1972-1976) for which he served as chief negotiator; and his directorship of studies on Asia sponsored by the United States Association of Former Members of Congress and coeditorship of a comparative study of the Japanese Diet (Kokkai) and the U.S. Congress (1983).
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Secretary of the U.S. Senate and foreign affairs consultant.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Mansfield, Mike, -- 1903-2001.; Democratic Party (U.S.); Japan. -- Kokkai; Library of Congress. -- Legislative Reference Service; United States. -- Commission on the Operation of the Senate; United States. -- Congress; United States. -- Congress. -- Senate -- Officials and employees; United States Association of Former Members of Congress; Vietnam War, 1961-1975.; Asia -- Politics and government -- 1945-; China -- Economic conditions -- 20th century; China -- Foreign relations -- United States; China -- History, Military -- 20th century; China -- Politics and government -- 1945-1949.; China -- Politics and government -- 1949-; Japan -- Economic conditions -- 1945-; Japan -- History, Military -- 1945-; Japan -- Politics and government -- 1945-; Korea -- Economic conditions -- 1945-; Korea -- History, Military; Korea -- Politics and government; Philippines -- Economic conditions -- 1946-1986.; Philippines -- History, Military; Philippines -- Politics and government -- 1946-; United States -- Foreign relations -- China; United States -- Foreign relations -- East Asia; United States -- Politics and government -- 1945-; Consultants; Secretaries, U.S. Senate